From Chain‐ to Graphene‐like Hydroxyl‐terminated (ZnO)n Clusters with n≤6 Obtained via Zinc Dimethoxide Hydrolysis and Condensation: Ab initio Structural, Electronic, Vibrational and Optical Properties Calculations. Issue 9 (31st March 2021) - Romero, Mariano; Mombrú, Dominique; Pignanelli, Fernando; Faccio, Ricardo; Mombrú, Álvaro W.
Abstract: Recent reports are focusing on the structural evolution from the atomic‐scale and also at the expenses of alkyl zinc alkoxide precursors towards (ZnO) n clusters and nanostructures with different interesting motifs, but still not much is known about their electronic properties. In this manuscript, we present a theoretical study using DFT and TD‐DFT methodologies on the hydrolysis and condensation of zinc dimethoxide precursor in its monomeric, dimeric and trimeric forms towards thermodynamically stable hydroxyl‐terminated (ZnO) n clusters with novel chain‐ and graphene‐like fashions. For all cases, distinct vibrational and optical spectra features were assigned evidencing a global monotonic decrease in the opto‐electronic gap with increasing oligomerization and cyclization stages. In addition, the electron‐affinity of all clusters was also observed to be enhanced with increasing oligomerization and cyclization stages and the electronic charge localization in ‐ e charged clusters was observed to be strongly related to the presence of zinc‐oxo subunits and other particular structural features. Our calculations also indicate that the stabilization through hydroxyl termination of both chain‐ and graphene‐like ZnO clusters not only could be a promising driving force to obtain larger atomic‐scale 1D and 2D nanostructures but also envisage interesting properties, particularly as electronic acceptor materials for energy applications. Abstract : Hydrolysis and condensation of zinc dimethoxide precursor in its monomeric, dimeric and trimeric forms towards thermodynamically stable hydroxyl‐terminated (ZnO) n clusters with novel chain‐ and graphene‐like structures were studied using DFT and TD‐DFT. Distinct vibrational and optical spectra features were assigned evidencing a global monotonic decrease in the opto‐electronic gap with increasing oligomerization and cyclization stages. The electron affinity of all clusters was also observed to be enhanced with increasing oligomerization and cyclization stages.